Report on Collection and Disposal of Refuse - Planning Commission, Government of India (Planning Commission, Government of India, 1964)
To achieve the objectives, this service has been developed and is doing developed on scientific lines. It is king highly mechanised demanding a high degree technical skill for efficient and economical performance. In fact, this long forgotten service is rapidly maturing in stature to become a professional service and science, it deserves to be.
Committee on Plan Projects (Building Projects Team)
Committee on Plan Projects (Building Projects Team)New Delhi
Keywords: Refuse and garbage disposal